Comparative study of anonymous network Tor and I2P - Yun YANG; Lingyan LI; Qingzheng WEI (网络与信息安全学报)
Tor is the most deployed anonymous communication system,providing online anonymity and privacy protection,while the invisible Internet project allows applications to send messages to each other anonymously and securely by using garlic routing.The anonymous network Tor and I2P have been highly valued by the academic community and the industry,and are also welcomed by users.The key difference between the design concept between the Tor network and the I2P is that I2P attempts to transfer the existing Internet service to the I2P network,and service implementation is provided within the framework,while Thor allows anonymous access to implement and operate external Internet services separately.The anonymous networks Tor and I2P in terms of terminology,project development,anonymous services,key technologies,threat types,etc.were compared,revealing the inherent and essential differences between the two anonymous networks.